English – Majored Students’ Perceptions on Teachers’ Use Of Vietnamese In EFL Classrooms - Phuong Hoang Yen; Dang Thanh Danh (Lembaga Penelitian dan Pengabdian Masyarakat IAIN Kediri, 2021)
Previous studies were conducted to discover the use of L1 in EFL classrooms, however, few studies investigated the students’ perception towards the teachers’ use of L1 in EFL classrooms, especially those for English – majored students. The present study was conducted to examine English – majored students’ perceptions towards their teachers’ use of mother tongue as Vietnamese in EFL classrooms in a university in Mekong Delta, Vietnam. The research was designed as a descriptive study with the mixed method using questionnaire and interview as the research instruments. There were 131 participants in this research. The findings of the study revealed that students preferred teachers’ use of mother tongue in the specialized classes (linguistics course, literal courses, and interpretation and translation courses, etc.), grammar courses, and some activities such as explaining incomprehensible words. However, they wished to have more English instruction in language skills classes to enhance their target language proficiency. Several disadvantages of using Vietnamese were also mentioned, for instance, hindering learners’ language improvement, causing their laziness and passiveness. Suggestions are proposed to raise EFL teacher’s awareness on the extent of English and Vietnamese in their teaching to help leaners achieve objective of the class.